2021
DOI: 10.1111/dmcn.15024
|View full text |Cite
|
Sign up to set email alerts
|

Early motor outcomes in infants with critical congenital heart disease are related to neonatal brain development and brain injury

Abstract: ABBREVIATIONS AISArterial ischaemic stroke Bayley-III-NL Bayley Scales of Infant and Toddler Development, Third Edition (Dutch) CCHD Critical congenital heart disease CGM Cortical grey matter CST Corticospinal tract DTI Diffusion tensor imaging UMW Unmyelinated white matter WMI White matter injury AIM To assess the relationship between neonatal brain development and injury with early motor outcomes in infants with critical congenital heart disease (CCHD).METHOD Neonatal brain magnetic resonance imaging was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 29 publications
2
37
0
Order By: Relevance
“…Stegeman et al described neonatal cortical gray matter and cerebellar volume but not unmyelinated white matter being associated with fine motor scores at 9 and 18 months of age. 42 Again, these effects were small. 42 Bonthrone et al reported a significant association between a neonatal atypicality index, representing the deviation of brain volumes from typical neonatal brain development, and the Bayley cognitive composite scores at 22 months of age.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Stegeman et al described neonatal cortical gray matter and cerebellar volume but not unmyelinated white matter being associated with fine motor scores at 9 and 18 months of age. 42 Again, these effects were small. 42 Bonthrone et al reported a significant association between a neonatal atypicality index, representing the deviation of brain volumes from typical neonatal brain development, and the Bayley cognitive composite scores at 22 months of age.…”
Section: Discussionmentioning
confidence: 96%
“…42 Again, these effects were small. 42 Bonthrone et al reported a significant association between a neonatal atypicality index, representing the deviation of brain volumes from typical neonatal brain development, and the Bayley cognitive composite scores at 22 months of age. 43 Sadwani et al reported that fetal total and regional brain volumes explained 10% to 21% of variance in cognitive, language, and motor development at 2 years of age.…”
Section: Discussionmentioning
confidence: 96%
“…Quality, as assessed with the CASP checklists, was found to be sufficient in all included studies. Level of evidence was rated as level 3 for 17 studies 18,29–44 and level 4 for one study 45 …”
Section: Resultsmentioning
confidence: 99%
“…By using the National Institutes of Health Quality Assessment Tool to score risk of bias, 28 of the 17 cohort studies, we rated one as ‘good’, 38 eight as ‘good/fair’, 18,29–32,40,43,44 and eight as ‘fair’ 33–37,41,42,45 . No cohort studies were rated as poor.…”
Section: Resultsmentioning
confidence: 99%
“…A study investigating cognitive functioning in preschool children following the Fontan procedure found that survivors have low-average performance but, in most cases without comorbid genetic disorders, are not severely impaired 28 . Studies of children who have undergone surgery requiring cardiopulmonary bypass in the neonatal period have found increased risk for motor and behavioral problems versus term children or very preterm children without CHD 29,30 . Domains that have been deemed at higher risk are visuomotor integration, processing speed, and executive functioning, including inattention, hyperactivity, and behavioral problems 15,18,26,28,[31][32][33][34] .…”
mentioning
confidence: 99%